1991
DOI: 10.1073/pnas.88.15.6805
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor beta 1, a potent chemoattractant for human neutrophils, bypasses classic signal-transduction pathways.

Abstract: Transforming growth factor .1 (TGF-fl1), a homodimeric polypeptide (Mr 25,000), derives from inflammatory cells and acts as a chemoattractant for monocytes and fibroblasts. We report here that TGF-131 is also the most potent chemoattractant yet described for human peripheral blood neutrophils. Recombinant TGF-,t1 elicited dose-dependent directed migration of neutrophils under agarose that was inhibited in the presence of a neutalizing antibody to TGF-j91.Maximal chemotaxis was evoked by TGF-181 at femtomolar c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
101
1
4

Year Published

1992
1992
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(118 citation statements)
references
References 40 publications
12
101
1
4
Order By: Relevance
“…TGFb1 exerts a potent chemotactic effect in neutrophils (44,45). Many cell types, including immune cells, produce TGFb1, which is secreted in a latent form bound to various proteins (45).…”
Section: Discussionmentioning
confidence: 99%
“…TGFb1 exerts a potent chemotactic effect in neutrophils (44,45). Many cell types, including immune cells, produce TGFb1, which is secreted in a latent form bound to various proteins (45).…”
Section: Discussionmentioning
confidence: 99%
“…This subset of innate immune cells has important functions in infection and inflammation, and includes neutrophils, eosinophils, and basophils. TGF-b induces chemotaxis of both neutrophils (Brandes et al 1991;Fava et al 1991;Reibman et al 1991) and eosinophils (Luttmann et al 1998). At the molecular level, Smad3 may be required for TGFb-induced neutrophil migration, as Smad3 2/2 neutrophils show impaired chemotactic responses (Yang et al 1999).…”
Section: Granulocytesmentioning
confidence: 99%
“…TGFβ was also shown to prevent the production of ROS, reactive nitrogen intermediates and IL-1β by neutrophils [86]. Furthermore, TGFβ has even been shown to be a potent chemoattractant for neutrophils taking a central part in their recruitment to sites of inflammation [87][88][89]. However, another study showed that TGFβ reduces the expression of the adhesion molecule L-Selectin, resulting in impaired neutrophil recruitment to sites of inflammation [86].…”
Section: Tgfβmentioning
confidence: 99%